Analisis Penerapan Teori Antrian pada Usaha Nasi Bebek Pedas Khas Madura Nor Aini - Rina Nurhidayati; Nur Arifiya; Galuh Candra Widi Putri; Kelvin Gilang Nugraha; Yakub Yakub (Neolectura, 2022)
This study analyzes the queuing system at the Madura Nor Aini Spicy Duck Rice Business. The analysis uses data on the speed of customer arrivals and data on the speed of customer service to get a queuing model and characteristics at the Madura Nor Aini Spicy Duck Rice Business. The research method used is quantitatively based on primary data and uses a stopwatch to record service time data. The results of this study are the queuing model, namely (M/M/1): (FIFO/ / ) with the arrival of people while waiting for the average is 2 people, the average number of people while waiting and queuing is 3 people, the average time while waiting is 19.2 minutes, the average time while waiting and queuing is 13.2 minutes, and the level of busyness is 70%. So, it can be concluded that this situation can be said to be quite ideal for the queue system at the Madura Nor Aini Spicy Duck Rice Business. However, the business needs to be increased again, so that the owner's level of activity increases to reach 100% and his popularity and profits also increase. Keywords: Queuing, Arrival, Service